2019
DOI: 10.1111/jonm.12833
|View full text |Cite|
|
Sign up to set email alerts
|

A descriptive study to analyse the disaster preparedness among Saudi nurses through self‐regulation survey

Abstract: Aim The present study aimed to analyse the disaster preparedness among Saudi nurses through self‐regulation survey. Background Nurses along with other healthcare professionals face difficulty in terms of management during disastrous condition. Moreover, there is a need to improve the abilities of nurses in managing disaster events by examining the disaster preparedness of nurses. Methods It employed quantitative descriptive design by conducting a self‐regulation survey among 350 nurses recruited from five gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…In contrast, response competencies differed by participants' age, education level, rank and career length. These results correspond to the findings of a previous study that reported differences by nurses' age, career length, rank and disaster experience (Baker, Alamri, & Aboshaiqah, 2019;Taskiran & Baykal, 2019). For future studies, nursing position differences should be measured to identify whether the differences arise from roles and responsibilities in an emergency or from increased training opportunities.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, response competencies differed by participants' age, education level, rank and career length. These results correspond to the findings of a previous study that reported differences by nurses' age, career length, rank and disaster experience (Baker, Alamri, & Aboshaiqah, 2019;Taskiran & Baykal, 2019). For future studies, nursing position differences should be measured to identify whether the differences arise from roles and responsibilities in an emergency or from increased training opportunities.…”
Section: Discussionsupporting
confidence: 86%
“…Hospital employees must have proper recognition and response competencies regarding emergency codes to secure the safety of themselves, patients and visitors when emergency codes are activated. Since nurses comprise the largest component of hospital employees and work closely with patients, their disaster response competencies are vital; yet, their disaster preparedness levels are poor, and most nurses are not confident about their ability to respond to disasters (Baack & Alfred, 2013;Baker, Alamri, Aboshaiqah, 2019;Labrague et al, 2018;Usher et al, 2015). Moreover, because of the global COVID-19 outbreak, nurses are at a high risk of infection even though they wear personal protective equipment (Huang, Lin, Li, Yu, & Zhou, 2020).…”
mentioning
confidence: 99%
“…As a result of this review, four themes were most commonly extracted in relation to disaster nursing education in Saudi Arabia: (A) There is an insu cient number of disaster simulations and drills for nurses related to disaster training, and this has a signi cant impact on the con dence of nurses in responding to a disaster (16,(18)(19)(20). (B) Disaster nursing is not yet fully incorporated into nursing programs' curricula, as the reviewed studies indicated that there is a lack of formal disaster education and training in nursing curricula and that more effort is needed to provide innovative training (16,19,21).…”
Section: Extraction and Resultsmentioning
confidence: 99%
“…(C) There is inadequate disaster knowledge and skills among nurses in Saudi Arabia (16,18,22). Finally, (D) the lack of educational and training resources for disaster nursing identi ed in the articles results in di culty in nding guidelines related to disaster management in Saudi Arabia; guidelines and protocols are also not easily accessible by staff, and it is di cult to nd and access articles and textbooks related to disaster management (16,21,22).…”
Section: Extraction and Resultsmentioning
confidence: 99%
“…In the article by Baker et al (2019), the information in the acknowledgments section was incomplete.…”
mentioning
confidence: 99%